2012
DOI: 10.1038/mtna.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile Changes After Short-activating RNA-mediated Induction of Endogenous Pluripotency Factors in Human Mesenchymal Stem Cells

Abstract: It is now recognized that small noncoding RNA sequences have the ability to mediate transcriptional activation of specific target genes in human cells. Using bioinformatics analysis and functional screening, we screened short-activating RNA (saRNA) oligonucleotides designed to target the promoter regions of the pluripotency reprogramming factors, Kruppel-like factor 4 (KLF4) and c-MYC. We identified KLF4 and c-MYC promoter-targeted saRNA sequences that consistently induced increases in their respective levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…Our results indicate that RNAa-mediated OCT4 activation works consistently in a panel of human MSCs that we tested. Other groups have also shown that promoter-targeted saRNAs could consistently induce endogenous KLF4 and c-MYC expressions in human MSCs derived from bone marrow [33]. Taken together, these observations suggest that saRNA-mediated gene activation could effectively upregulate endogenous pluripotent factors in human MSCs.…”
Section: Upregulation Of Oct4 Expression In Human Mesenchymal Stem Bymentioning
confidence: 65%
“…Our results indicate that RNAa-mediated OCT4 activation works consistently in a panel of human MSCs that we tested. Other groups have also shown that promoter-targeted saRNAs could consistently induce endogenous KLF4 and c-MYC expressions in human MSCs derived from bone marrow [33]. Taken together, these observations suggest that saRNA-mediated gene activation could effectively upregulate endogenous pluripotent factors in human MSCs.…”
Section: Upregulation Of Oct4 Expression In Human Mesenchymal Stem Bymentioning
confidence: 65%
“…Similarly, small RNA-induced TGA has been reported in mammalian systems Watts et al 2010;Voutila et al 2012;Matsui et al 2013;Reebye et al 2013a,b), though the molecular mechanisms have not been fully elucidated. In these previous studies, TGA has been induced by two or more shRNAs that target the promoter sequence (Chu et al 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Despite these and other demonstrations of mammalian TGA (Place et al 2008;Matilainen et al 2010;Matsui et al 2010;Voutila et al 2012;Reebye et al 2013a,b), the molecular mechanisms of the process are still not well understood, including the details about the role of lncRNAs in TGA and whether they act in an allele-specific cis-mode or a trans-mode. In this study, we devised a TGA model based on CMV-EGFP reporter gene system to investigate the factors required for TGA.…”
Section: Introductionmentioning
confidence: 98%
“…[ 7 ]. This concept, again, is subjective, as there is evidence to show that transcription factors that are able to drive pluripotency can be induced by saRNAs in human mesenchymal stem cells [ 37 ]. The Ago2 processing unit has also created some dispute, where it is thought that Ago2-induced degradation of the strand does not emerge on the noncoding transcript of the target gene.…”
Section: Target Site Selection Of Sarnamentioning
confidence: 99%
“…The ability to modulate pluripotent reprogramming factors, such as Kruppel-like factor 4 (KFL4) and c-Myc, by synthetic saRNA is likely to accelerate stem cell research [ 37 ]. Combined expression of OCT3/4, SOX2, KLF4, and c-Myc already allows reprogramming of adult fi broblasts into induced pluripotent stem cells for a myriad of applications [ 42 ].…”
Section: Stem Cell Differentiationmentioning
confidence: 99%